Application of window Malmquist index for examination of efficiency change of Czech commercial banks - Iveta Palecková (DANUBE: Law, Economics and Social Issues Review, 2017)
The aim of the paper is to apply the Window Malmquist index approach to examine the efficiency change of Czech commercial banks within the period 2004-2013. We used the Data Envelopment Analysis and theWindow Malmquist index approaches to estimate the efficiency change of Czech commercial banks. The average efficiency computed under the assumption of constant returns to scale was 73% and under the assumption of variable returns to scale the value was 83%. We estimated the average positive efficiency growth of Czech commercial banks during the period 2004-2013. We found that average scale efficiency was 88%, which means that Czech commercial banks were of an inappropriate size, especially the largest banks.
Keywords: 330; Banking sector; Czech Republic; Data Envelopment Analysis; Window Malmquist Index